SEMANTIC ANALYSIS OF PHRASES LINKED WITH “HEALTH” (Web of Teachers: Inderscience Research, 2026)
Using semiotic analysis, this article identifies key cultural domains underlying the formation of phraseological units related to human vitality and well-being. The study establishes several semiotic areas that structure the semantic organization of phraseology: care, energy, abundance, endurance, youth, freshness, cheerfulness, and norm.